Text message-based lifestyle intervention in primary care patients with hypertension: a randomized controlled pilot trial - Beata Borgström Bolmsjö; Moa Wolff; Veronica Milos Nymberg; Magnus Sandberg; Patrik Midlöv; Susanna Calling (Taylor & Francis Group, 2020)
Objective To evaluate the feasibility of a randomized controlled pilot study with lifestyle-promoting text messages as a treatment for hypertension in primary care. Design Randomized controlled pilot trial. Setting Three primary health care centers in southern Sweden. Subjects Sixty patients aged 40-80 years with hypertension were included. Main outcome measures Feasibility of the pilot study, i.e. recruitment rate, dropout rate and eligibility criteria. Secondary outcomes were change in blood pressure and other cardiovascular risk factors. Methods Thirty participants were randomized to the intervention group with four lifestyle-promoting text messages sent every week for six months. The control group received usual care. The baseline and follow-up visits for all 60 patients included measurements of blood pressure, anthropometrics, blood tests and a self-reported questionnaire. Results All feasibility criteria (recruitment rate (≥55%), dropout rate (≤15%) and eligibility (60 eligible patients during the four-month inclusion period) for the pilot study were fulfilled. This means that a larger study with a similar design may be conducted. After six months, there were no significant improvements in cardiovascular risk factors. However, we found favorable trends for all secondary outcomes in the intervention group as compared to the control group. Conclusion Lifestyle modification in patients with hypertension is important to reduce cardiovascular risk. However, primary healthcare has limited resources to work with modifying lifestyle habits. This is the first pilot study to test the feasibility of text message-based lifestyle intervention in patients with hypertension in Swedish primary healthcare. Whether significant improvement in cardiovascular risk factors may be achieved in a larger study population remains to be evaluated.Key points This pilot randomized controlled trial (RCT) is the first study to evaluate the feasibility of text message-based lifestyle advice to patients with hypertension in Swedish primary healthcare. •All feasibility criteria for the pilot study were fulfilled. This outcome means that a larger study with a similar design may be conducted. •The study was not powered to find significant changes in cardiovascular risk factors. Nevertheless, after six months we found favorable trends for all secondary outcomes in the intervention group compared to control. •If a future larger study can show significant results, this intervention could serve as a useful tool in everyday primary healthcare.